Cutting edge research methods in hospitality and tourism - Okumus, Fevzi; Rasoolimanesh, S. Mostafa; Jahani, Shiva (Emerald Publishing Limited, 2023)
Cutting Edge Research Methods in Hospitality and Tourism sits at the forefront of fast-paced developments in the tourism and hospitality industry, highlighting the importance of applied and pure research to address the theoretical and practical problems and gaps. Approaching from different perspectives including economic, social, cultural, environmental, political, and technological, this edited collection reviews traditional research methods and re-assesses them to suit contemporary problems and research agendas. Developing recent research strategies under the umbrella of quantitative and qualitative research methods - such as the use of structural equation modeling analysis, applied econometric research, network theory and social network analysis, using tracking mobility and planning exercises, fuzzy-set Qualitative Comparative Analysis, necessary condition analysis, and netnography approaches - can offer promising solutions. A necessity for academics and practitioners in the tourism and hospitality sector, Cutting Edge Research Methods in Hospitality and Tourism expands existing knowledge, generating innovative research.
Keywords: Tourism -- Research -- Methodology.; Hospitality industry -- Research -- Methodology.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Tourism industry.; elektronické knihy; electronic books